Fabrication of eugenol loaded gelatin nanofibers by electrospinning technique as active packaging material. (March 2021) - Li, Mi; Yu, Hang; Xie, Yunfei; Guo, Yahui; Cheng, Yuliang; Qian, He; Yao, Weirong
Abstract: The aim of this work was to develop a novel degradable bioactive film with poly (lactic acid), gelatin and eugenol, and electrospinning technology was used to develop an active internal layer for the active films to encapsulate eugenol. An annealing treatment was used to improve the adhesion of the active layer onto the poly (lactic acid) film. The results showed that eugenol could be efficiently encapsulated in nanofibers (92.72 g/100 g). The internal active layer containing it showed a uniform fiber morphology observed by scanning electron microscope. The diameter of nanofibers was enlarged and the hydrophobicity was enhanced, the antioxidant activity and antibacterial activity were improved as the addition of eugenol compared with pure gelatin nanofibers. In particular, nanofibers containing 4 μL/mL eugenol (G3) showed the highest antioxidant activity (32.99 mg DPPH/g dry weight), radical scavenging activity (43.80%), and significant microbial growth inhibition with CFU of about 3 log units ( E. coli ) and 2.5 log units ( S. aureus ) lower than the control. In conclusion, our results suggested that active layer could be an effective method to encapsulate eugenol, and the poly (lactic acid)/gelatin nanofibers bilayer film was a novel biodegradable packaging material with excellent antioxidant activity and antibacterial activity. Highlights: Electrospinning was used to develop active internal layer for composite film. Eugenol was encapsulated in nanofibers and enhanced its hydrophobicity. The composite film is a novel biodegradable material for active packaging.